The impact of English oak (Quercus robur L.) acorn storing methods on their germination and standard planting stock output - Андрусяк , Ю. І. (Forestry and Forest Melioration, 2022)
Introduction It is well known that the economic value and biological resistance of oak (Quercus robur L.) stands grown from acorns is significantly higher compared to those established with seedlings. Therefore, establishing oak stands by sowing acorns is highly promising, especially for the areas with no natural regeneration of oak. The aim of the study was to assess the influence of the pre-sowing storage methods for English oak acorns on their germination. Materials and Methods During the study, we used the silvicultural method (establishment of quality indicators for acorns, planting stock and forest crops), biometric (defining of growth indicators and mass of planting stock), and classical statistical one. To ensure reliable reforestation of Q. robur plants in the areas with insufficient or nonexistent natural regeneration in Bukovyna Subcarpathia, in the autumn of 2020, we collected 2,000 acorns of common oak and 2,000 acorns from the plus trees with improved hereditary qualities in Valya-Kuzminske Forestry in the Chernivtsi State Forest Enterprise. Then we selected and calibrated 1,000 acorns of the same size in each group. It was done using a caliper with tolerances of ±0.1 mm in diameter and ±0.5 mm in length. The next stage was the division of the acorns into three parts (333 acorns each). At that, one part was stored in a trench in the traditional way; the second one was stored in a cellar in the sand where moisture content was maintained at the level of 60–65% of the total moisture capacity. The third part was stored in running water. Results and Conclusions The study revealed that the largest number of acorns with the potential of germination, the highest field germination rate and the output of oak standard planting stock were registered for pre-sowing storage of acorns by the traditional “trench method” and in “running water” (respectively 87–89% of the seeds of local origin and 89–90% of the acorns which possessed improved hereditary properties). The acorns that were stored in a sand cellar had the lowest yield of standard planting stock (43–44%) and the highest proportion of dead seedlings (26%). The obtained results indicate the need for further research in order to clarify the depth of sowing of English oak acorns in the autumn after collection and the specifics for the use of various pesticides against rhizophagous pests. 1 Fig., 2 Tables, 7 Refs.